2007
DOI: 10.1002/jpln.200625203
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of salinity and potassium availability on growth, water status, and ionic composition of Hordeum maritimum

Abstract: The interactive effects of salinity and potassium (K+) availability on biomass production, water status, and ionic composition were investigated in Hordeum maritimum, an annual grass growing natively on saline soils. Plants were grown for 7 weeks on Hewitt nutrient solution supplied with NaCl (0, 100, 150, 200, and 300 mM) combined with low (0.232 mM) or high (5.8 mM) K+ levels. Independent of potassium availability, dry matter of both roots and shoots decreased consistently with increasing NaCl levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 22 publications
9
40
0
Order By: Relevance
“…S plants is very efficient. These findings are consistent with those of Hafsi et al (2007) who showed that the osmotic effect was limited in H. maritimum and found that tissue water content remained relatively high in shoots (80% of fresh weight) even at 300 mM NaCl. It is remarkable that despite this enhancement of stomatal closure, instantaneous CO 2 assimilation rate quantified in the presence of salt and low P (A) was surprisingly increased by NaCl in young leaves of P-deficient plants.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…S plants is very efficient. These findings are consistent with those of Hafsi et al (2007) who showed that the osmotic effect was limited in H. maritimum and found that tissue water content remained relatively high in shoots (80% of fresh weight) even at 300 mM NaCl. It is remarkable that despite this enhancement of stomatal closure, instantaneous CO 2 assimilation rate quantified in the presence of salt and low P (A) was surprisingly increased by NaCl in young leaves of P-deficient plants.…”
Section: Discussionsupporting
confidence: 94%
“…Na ? ) of the ion concentrations (mM) in the nutrient medium of H. maritimum shoots (Hafsi et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in saline soils, plants may suffer from a dual injury: sodium toxicity and potassium deficiency (Rubio et al 1995;Schachtman 2000) owing to competition between potassium and sodium ions to enter plant cells because they are similar in ionic radius and ion hydration energies (Schachtman and Liu 1999). The annual facultative halophyte Hordeum maritimum, potentially useful for forage production in saline zones, can survive up to 300 mM NaCl under potassium-deficient conditions (Hafsi et al 2007). As this species is tolerant to K ?…”
Section: Introductionmentioning
confidence: 99%
“…; Family Poaceae). This is a Mediterranean wild grass typical of saline coastal or inland meadows (Lombardi and Lupi 2006), making it potentially useful for fodder production in saline zones (Hafsi et al 2007).…”
Section: Introductionmentioning
confidence: 99%